2005
DOI: 10.1016/j.neuron.2005.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Adaptation and Representation in Human Early Visual Cortex

Abstract: The human visual system can distinguish variations in image contrast over a much larger range than measurements of the static relationship between contrast and response in visual cortex would suggest. This discrepancy may be explained if adaptation serves to re-center contrast response functions around the ambient contrast, yet experiments on humans have yet to report such an effect. By using event-related fMRI and a data-driven analysis approach, we found that contrast response functions in V1, V2, and V3 shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
134
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(151 citation statements)
references
References 81 publications
15
134
2
Order By: Relevance
“…The results, when superimposed on retinotopic maps of individual subjects, revealed that the reduced activations were seen as early as V1 but mainly in V3-V4 and beyond, all of which contain populations of neurons that are sensitive to stimulus contrast (Boynton et al, 1999;Reynolds et al, 2000;Gardner et al, 2005;Lu and Roe, 2007). Previous studies reported perceptual learning effects in early visual areas, including V1 and V4, when subjects were trained on fine discriminations of simple visual features, such as orientation and texture (Schiltz et al, 1999;Schoups et al, 2001;Schwartz et al, 2002;Furmanski et al, 2004;Yang and Maunsell, 2004;Sigman et al, 2005;Raiguel et al, 2006), and in motion-sensitive areas MT and MST, when subjects were trained on motion discrimination tasks (Zohary et al, 1994;Vaina et al, 1998).…”
Section: Changes In Visual Cortex Activation During Perceptual Learningmentioning
confidence: 99%
“…The results, when superimposed on retinotopic maps of individual subjects, revealed that the reduced activations were seen as early as V1 but mainly in V3-V4 and beyond, all of which contain populations of neurons that are sensitive to stimulus contrast (Boynton et al, 1999;Reynolds et al, 2000;Gardner et al, 2005;Lu and Roe, 2007). Previous studies reported perceptual learning effects in early visual areas, including V1 and V4, when subjects were trained on fine discriminations of simple visual features, such as orientation and texture (Schiltz et al, 1999;Schoups et al, 2001;Schwartz et al, 2002;Furmanski et al, 2004;Yang and Maunsell, 2004;Sigman et al, 2005;Raiguel et al, 2006), and in motion-sensitive areas MT and MST, when subjects were trained on motion discrimination tasks (Zohary et al, 1994;Vaina et al, 1998).…”
Section: Changes In Visual Cortex Activation During Perceptual Learningmentioning
confidence: 99%
“…Prior presentation of a grating in the receptive field of a simple cell in the visual cortex elevates that unit's contrast threshold and shifts its contrast sensitivity function toward higher contrasts (e.g., Carandini & Ferster, 1997). Similar effects have also been found for behavioral measures of contrast sensitivity (e.g., Gardner et al, 2005;Pestilli, Viera, & Carrasco, 2007). Hence, the visual system's response to a grating is affected by its recent history of exposure to different levels of contrast.…”
mentioning
confidence: 58%
“…In other words, the unit's contrast sensitivity is adjusted to permit it to function effectively over a large range of ambient contrasts. A number of studies, both behavioral (e.g., Boynton & Foley, 1999;Foley, 1994;Ross & Speed, 1991;Wilson & Humanski, 1993) and neural (e.g., Albrecht & Geisler, 1991;Albrecht & Hamilton, 1982;Gardner et al, 2005;Ohzawa, Sclar, & Freeman, 1982), have found evidence for the existence of a contrast sensitivity control mechanism. They have demonstrated that contrast sensitivity in a confined region of the visual field is modulated by the spatial and temporal frequency composition of nearby stimuli (see, e.g., Foley, 1994, for details on the mechanism).…”
mentioning
confidence: 99%
“…have also revealed contrast sensitivity and gain-control in the human visual cortex, including areas V1, V2, V3, V4 and MT (Avidan et al, 2001;Boynton et al, 1999;Gardner et al, 2005;Heeger et al, 2000;Tootell et al, 1995;. In these studies, the 'response' variable is the hemodynamic or blood-oxygen-level dependent (BOLD) signal that depends on the activity of many neurons.…”
Section: Neuroimaging Techniques Such As Functional Magnetic Resonancmentioning
confidence: 99%
“…This serves to center the CRF on the average ambient level of contrast (e.g. Gardner et al, 2005;Ohzawa et al, 1982), effectively shifting the dynamic range. Graphically, this corresponds to a lateral shift of the CRF, which can be modeled by changing the value of x 50 .The second is that response-gain is adjusted through a multiplication of the response by a constant factor proportional to the average ambient contrast (e.g.…”
Section: Introductionmentioning
confidence: 99%